2023
DOI: 10.1017/s0031182023000136
|View full text |Cite
|
Sign up to set email alerts
|

Putative chemical cue fromGyrodactylus-infected guppies subtly alters behaviour but prior exposure decreases parasite intensity

Abstract: The reliance on chemical communication is well established for evading predation in aquatic systems. Only a few studies have found evidence that chemical cues released from aquatic animals infected with parasites alter behaviour. Furthermore, the link between putative chemical cues and susceptibility to infection has not been studied. The objectives of this study were to determine if exposure to chemical cues from Gyrodactylus turnbulli-infected guppies (Poecilia reticulata) at various times post-infection res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, amphipods that were infected with C. parvum metacercariae were more likely to acquire more metacercariae, indicating that an existing infection promoted reinfection, a phenomenon that has been reported in other invertebrate infections. In contrast, di Bacco & Scott (2023) reported that prior exposure to a putative chemical cue released by G. turnbulli -infected guppies delayed and dampened transmission in experimental epidemics.…”
Section: The Parasite Lensmentioning
confidence: 96%
“…However, amphipods that were infected with C. parvum metacercariae were more likely to acquire more metacercariae, indicating that an existing infection promoted reinfection, a phenomenon that has been reported in other invertebrate infections. In contrast, di Bacco & Scott (2023) reported that prior exposure to a putative chemical cue released by G. turnbulli -infected guppies delayed and dampened transmission in experimental epidemics.…”
Section: The Parasite Lensmentioning
confidence: 96%
“…First, a cue must be produced either directly by a parasite or something associated with risk of infection; for example, the avoidance of faeces which may or may not be infested with parasites. Individuals can detect different types of cues depending on the host and parasite, including chemosensory cues (Di Bacco & Scott, 2023;Kavaliers et al, 2004), visual cues such as behavioural changes (Dugatkin et al, 1994) or physical signs of the pathology (Kennedy et al, 1987;Rosenqvist & Johansson, 1995), as well as other types of cues (e.g., vibratory display of infected termites: Rosengaus et al, 1999). Second, hosts must have the capacity to detect cues; the physiological mechanisms to interpret and recognize the cue are required for the cue to be perceived by the host within the landscape of disgust (e.g., detection of chemical cues in mice: Kavaliers et al, 2004).…”
Section: Defining the Landscape Of Disgustmentioning
confidence: 99%
“…Parasite recognition mechanisms are diverse, but may involve visual cues, such as abnormal host behaviour, visibility of the parasite itself, or physical changes like color patterns, (Behringer et al, 2018; Krause & Godin, 1996; Lopes et al, 2022) and chemical cues, such as pheromones, metabolites and alarm substances (Chivers et al, 2007; Di Bacco & Scott, 2023; Kamio et al, 2022; Stephenson et al, 2018; Yao et al, 2009). In aquatic environments, visual cues are effective for rapid communication, especially in areas where view is unobstructed.…”
Section: Introductionmentioning
confidence: 99%